Whole-Body Magnetic Resonance Imaging Assessment of Joint Inflammation in Rheumatoid Arthritis—Agreement With Ultrasonography and Clinical Evaluation - Ng, Sin Ngai; Axelsen, Mette B.; Østergaard, Mikkel; Pedersen, Susanne Juhl; Eshed, Iris; Hetland, Merete L.; Møller, Jakob M.; Terslev, Lene (Frontiers in Medicine, 2020)
Objective: To compare joint inflammation seen by whole-body magnetic resonance imaging (WBMRI), with “whole-body” ultrasound and clinical assessments, in patients with active rheumatoid arthritis (RA) before and during tumor necrosis factor-inhibitor (TNF-I, adalimumab) treatment. Methods: In 18 patients with RA, clinical assessment for joint tenderness and swelling, WBMRI and ultrasound were obtained at baseline and week 16. Wrist, metacarpophalangeal (MCP) and proximal interphalangeal (PIP), elbow (except for WBMRI), shoulder, knee, ankle and metatarsophalangeal joints were examined. Joint inflammation was defined by WBMRI as the presence of synovitis and/or osteitis and by ultrasound as grey-scale synovial hypertrophy grade >2 and/or color Doppler grade >1. On patient level, agreement was assessed by Spearman correlation coefficients (rho) for sum scores for 28 joints (i.e. wrists, MCPs, PIPs, elbows, shoulders, knees) between clinical examination (DAS28CRP), ultrasound (US28) and WBMRI (WBMRI26; elbows not included). On joint level, agreement on inflammation between WBMRI, ultrasound and clinical findings was calculated with Cohen’s kappa (κ). Results: At patient level, WBMRI26 and US28 sum scores showed good correlation (rho=0.72; p<0.01) at baseline, but not at follow-up (rho=0.25; p=0.41). At joint level, moderate agreement was seen for hand joints (κ=0.41-0.44); for other joints κ<0.40. No correlation with DAS28CRP was seen. No statistically significant correlations were observed between changes in WBMRI26, US28 and DAS28CRP during treatment. Conclusions: WBMRI and ultrasound joint inflammation sum scores at patient level showed good agreement in clinically active RA patients before TNF-I initiation, whereas agreement was poorer at joint level, and after treatment.